Phthalic acid derivatives: Sources and effects on the human body - Maria P. Sobolevskaya; Tatyana I. Vitkina; Dmitrii N. Cherenkov (Russian Open Medical Journal)
The review summarizes data on the sources of phthalates in the environment and the routes of their penetration into the human body (food and inhalation routes are described in detail). The article discusses methods for detecting phthalates in the human body and assessing adverse effects. Up-to-date information on the effects of phthalic acid derivatives on the human body is presented, potential health risks for people of different age groups are highlighted. Particular attention is paid to the adverse effects of phthalate derivatives on the respiratory system, especially in the context of inhalation of suspended particles contained in the atmospheric air.